The effects of diet on anatomy, physiology and health in the guinea pig - Witkowska, Agata; Price, Jennifer; Hughes, Chloe; Smith, Dulcie; White, Katie; Alibhai, Aziza; Rutland, Catrin S. (OMICS International, 2017)
Given the increasing popularity of the guinea pig as a pet, it is perhaps surprising that relatively little is published as to their husbandry and dietary requirements. Indeed, a review of the literature currently available to owners, scientists and clinicians alike has found it to be scarce, highly variable, and at times overtly contradictory. This review and data collection collates the husbandry and dietary information available and discusses the variable information available and the differing practices published in the literature in relation to the guinea pig. A questionnaire was also used to gather owner-reported data on feeding regimens from both the UK and Poland in order to better understand the range of feeding habits that owners employ. Despite the lack of information available in comparison with that available for other companion and livestock animals, advances in knowledge are being made. With guinea pig numbers increasing in many countries and owners seeking husbandry and veterinary advice and interventions, it is imperative that we understand guinea pig health and welfare issues. The data and review gives novel insights into how guinea pig husbandry affects health and welfare.